(untitled) (Inovasi: Jurnal Diklat Keagamaan, 2022)
English subject is taught not only for the regular students but also to students who have physical disorder especially to hearing impairment students. In Indonesia, there is a special school for these students called SLB (Sekolah Luar Biasa). In the teaching and learning proccess at SMP-LB (B), the teacher usually faces some difficulties dealing with the students because they have lack of their hearing system. the writer tried to dig up and find out the teacher and students interaction in English Class for Hearing Impairment Students in SMP-LB (B) Negeri Tuban and the students responses after the teacher apply certain interaction in the class at SMP-LB (B) Negeri Tuban. This study applied the qualitative case study research approach to answer the research questions. The study as conducted at SMP-(LB) Negeri Tuban which used three instruments such as observation, interview and documentation. The finding of the research showed that the teacher used Total Communication Technique which combines the oral and manual technique. Teacher not only used oral but also used sign language such as finger spelling, gestures, and facial expression. The writer also found one response after the teacher interaction in English class for Hearing Impairment Students such as Oral communication. Total communication Technique is expected to help them in teaching and learning of interaction in English to hearing impairment students in the right way appropiately. The teacher always gives good treatment to the students in order to able to reduce the problems in communication especially in listening and speaking.